N6-methyladenosine (m6A) RNA modification as a metabolic switch between plant cell survival and death in leaf senescence - Rudy, Elżbieta; Grabsztunowicz, Magda; Arasimowicz-Jelonek, Magdalena; Tanwar, Umesh Kumar; Maciorowska, Julia; Sobieszczuk-Nowicka, Ewa (Frontiers in Plant Science, 2023)
Crop losses caused by climate change and various (a)biotic stressors negatively affect agriculture and crop production. Therefore, it is vital to develop a proper understanding of the complex response(s) to (a)biotic stresses and delineate them for each crop plant as a means to enable translational research. In plants, the improvement of crop quality by m6A editing is believed to be a promising strategy. As a reaction to environmental changes, m6A modification showed a high degree of sensitivity and complexity. We investigated differences in gene medleys between dark-induced leaf senescence (DILS) and developmental leaf senescence in barley, including inter alia RNA modifications active in DILS. The identified upregulated genes in DILS include RNA methyltransferases of different RNA types, embracing enzymes modifying mRNA, tRNA, and rRNA. We have defined a decisive moment in the DILS model which determines the point of no return, but the mechanism of its control is yet to be uncovered. This indicates the possibility of an unknown additional switch between cell survival and cell death. Discoveries of m6A RNA modification changes in certain RNA species in different stages of leaf senescence may uncover the role of such modifications in metabolic reprogramming. Nonetheless, there is no such data about the process of leaf senescence in plants. In this scope, the prospect of finding connections between the process of senescence and m6A modification of RNA in plants seems to be compelling.